2016
DOI: 10.3389/fphys.2016.00151
|View full text |Cite
|
Sign up to set email alerts
|

Association with Amino Acids Does Not Enhance Efficacy of Polymerized Liposomes As a System for Lung Gene Delivery

Abstract: Development of improved drug and gene delivery systems directly into the lungs is highly desirable given the important burden of respiratory diseases. We aimed to evaluate the safety and efficacy of liposomes composed of photopolymerized lipids [1,2-bis-(tricosa-10,12-diynoyl)-sn-glycero-3-phosphocholine] associated with amino acids as vectors for gene delivery into the lungs of healthy animals. Lipopolymer vesicles, in particular, are more stable than other types of liposomes. In this study, lipopolymers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…It has been previously reported that polymeric liposomes have little interaction with DNA [ 23 ]. Recently, it has been shown that the mixture of the polymerizable diacetylenic lipid 1,2-bis(10,12-tricosadiynoyl)-sn-glycero-3-phosphocholine (DC 8,9 PC) and the lipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) (1:1) itself has the ability to transfect cells in vivo in mice [ 45 ] after being administered intratracheally. These results give the first indication that lipopolymers formulated with the diacetylenic lipid DC 8,9 PC might be used for in vivo DNA delivery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that polymeric liposomes have little interaction with DNA [ 23 ]. Recently, it has been shown that the mixture of the polymerizable diacetylenic lipid 1,2-bis(10,12-tricosadiynoyl)-sn-glycero-3-phosphocholine (DC 8,9 PC) and the lipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) (1:1) itself has the ability to transfect cells in vivo in mice [ 45 ] after being administered intratracheally. These results give the first indication that lipopolymers formulated with the diacetylenic lipid DC 8,9 PC might be used for in vivo DNA delivery.…”
Section: Introductionmentioning
confidence: 99%
“…En lo que se refiere a las adaptaciones cardiovasculares, se manifiestan después de dos a cuatro semanas de comenzar un entrenamiento, generando incremento en el gasto cardiaco máximo, que se encuentra correlacionado positivamente con las adaptaciones hematológicas [51]. Se evidencia que tanto el volumen de plasma como la sangre aumentan considerablemente [52] y la frecuencia cardiaca disminuye [53].…”
Section: Discussionunclassified
“…Liposomes as multilamellar vesicles (MLVs) were obtained by the dehydration-rehydration method, as previously described (Bandeira et al, 2016;Bangham, 1972;Julieta et al, 2013;Marsanasco, Márquez, Wagner, del V. Alonso, & Chiaramoni, 2011) Briefly, 10 mg of total lipids were dissolved in 0.2 mL of methanol. Then, the solvent was evaporated, and the film was resuspended in 1 mL of Phosphate Saline Buffer, pH 7.4 (PBS).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%